Biomarkers as targets for CAR-T/NK cell therapy in AML - Ruonan Shao; Zijian Li; Honglei Xin; Suyu Jiang; Yilin Zhu; Jingan Liu; Rong Huang; Kailin Xu; Xiaofeng Shi (BMC, 2023)
Abstract The most common kind of acute leukemia in adults is acute myeloid leukemia (AML), which is often treated with induction chemotherapy regimens followed by consolidation or allogeneic hematopoietic stem cell transplantation (HSCT). However, some patients continue to develop relapsed or refractory AML (R/R-AML). Small molecular targeted drugs require long-time administration. Not all the patients hold molecular targets. Novel medicines are therefore needed to enhance treatment outcomes. T cells and natural killer (NK) cells engineered with chimeric antigen receptors (CARs) that target antigens associated with AML have recently been produced and are currently being tested in both pre-clinical and clinical settings. This review provides an overview of CAR-T/NK treatments for AML.